Comparison of surgical outcomes of Ultrasonic technique (Harmonic Focus™) with Conventional technique in open hemithyroidectomy - Regmi, Deepak; KC, Toran; Bista, Meera; Shrestha, Sangita (Journal of Kathmandu Medical College, 2014)
Background: The option for dissection and haemostasis during thyroid surgery include either the modern ultrasonic technology (Harmonic Focus™) or the conventional technique using knot and ties, monopolar or bipolar electrocautery. Comparison between the surgical outcomes of open hemithyroidectomy using these two modalities was done.Objective: To compare the surgical outcomes of ultrasonic technique using Harmonic Focus™ (HS) with Conventional technique (CT) in open hemithyoidectomy.Method: Twenty consecutive patients undergoing open hemithyroidectomy for benign solitary thyroid nodule of ≤ 3 cm were randomly assigned into two groups; group HS (n=10) and group CT (n=10). Analysis of surgical outcomes performed by these two techniques, particularly: operative time, intra-operative blood loss, post operative pain, incision size, complications and hospital stay were done.Results: The age, sex and pathologies were comparable in both the groups. For the group HS, mean operative time was (mean ± SD=55 ± 5 min) 15 minutes shorter than group CT (mean ± SD= 70 ± 10 min) (P